Long-term integrated safety of patisiran in patients with hereditary transthyretin-mediated amyloidosis with polyneuropathy. (25th November 2020) - Gillmore, J; Berk, J; Dispenzieri, A; Polydefkis, M; Gonzalez-Duarte, A; Sekijima, Y; Sweetser, M.T; Arum, S; Wang, J.J; White, M.T; Maurer, M
Abstract: Background/Introduction: Hereditary transthyretin-mediated (hATTR) amyloidosis is a progressive, life-threatening disease; the majority of patients develop a mixed phenotype of polyneuropathy and cardiomyopathy. Patisiran halted or reversed polyneuropathy and improved quality of life in the Phase 3 (APOLLO) study. In a prespecified cardiac subpopulation of APOLLO, patisiran also improved cardiac structure and function versus placebo. Purpose: To describe the long-term comprehensive, integrated safety data from the patisiran clinical development program in patients with hATTR amyloidosis with polyneuropathy. Methods: Safety data as of October 7, 2019 from the Phase 2 Open-Label Extension (OLE) (NCT01961921), Phase 3 APOLLO (NCT01960348), and ongoing Global OLE (NCT02510261) studies were analysed. Results: Across the three studies, 224 patients received patisiran for a mean (range) of 43.6 (0.7–71.7) months, with a cumulative 813.9 patient-years of exposure; 105 (46.9%) patients received patisiran for ≥4 years and 35 (15.6%) patients received patisiran for ≥5 years. In this cohort, 149 (66.5%) had medical histories of cardiac disorders per MedDRA System Organ Class (SOC), which may be reflective of a mixed phenotype in some patients. A total of 222 (99.1%) patients experienced at least one adverse event (AE) and 132 (58.9%) patients experienced at least one serious AE. AEs considered to be related to patisiran and occurring in >5% of patients included infusion-related reactions (IRRs) (25.9%) and diarrhoea (6.3%). Cardiac AEs occurring in >5% of patients included atrial fibrillation (10.7%) and cardiac failure (7.6%). Amongst all patients, the exposure-adjusted mortality rate was 4.3 deaths per 100 patient-years. Conclusions: Patients with hATTR amyloidosis with polyneuropathy in the patisiran clinical development program represent those with the longest treatment with an RNAi therapeutic, including more than 15% of patients receiving patisiran for ≥5 years. Patisiran continues to demonstrate a positive benefit:risk profile in patients with hATTR amyloidosis with polyneuropathy. Funding Acknowledgement: Type of funding source: Private company. Main funding source(s): Alnylam Pharmaceuticals